Modified fly ash engineering material and preparation method and application thereof

CN122977771APending Publication Date: 2026-10-27CHINA HUADIAN ENG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611413779.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明提供了一种改性粉煤灰工程材料及其制备方法,以解决现有粉煤灰混凝土存在早期强度低、性能降低的问题

Benefits of technology

1.本发明提供的一种改性粉煤灰工程材料,以重量份数计,包括:基材100份,聚丙烯酰胺0.01-0.1份,混凝土速凝剂0.15-0.3份;基材中包括混凝土60-65份,粉煤灰35-40份。其中,混凝土提供主体强度、粘接性、成型性;粉煤灰中的活性SiO2、Al2O3会与水泥水化产生的氢氧化钙Ca(OH)2在碱性激发下,发生二次水化反应,生成水化硅酸钙(C-S-H)、水化铝酸钙等胶凝产物;这些产物不断填充孔隙、增强界面粘结,使混凝土后期强度持续增长,弥补早期强度偏低的不足。本发明添加的聚丙烯酰胺(PAM),利用其本身独特的分子结构与水泥体系的相互作用实现以下功能;①吸附与分散:长链分子吸附于水泥颗粒表面,通过电荷中和减少颗粒间静电排斥,促进絮凝与团聚;②网络形成:分子链相互交织形成三维网状结构,包裹水分子并增强水泥浆体凝聚力;③水化调控:与 Ca²+等水化产物形成络合物,影响水泥水化进程与产物形貌;④裂纹桥接:当混凝土受外力产生裂纹时,PAM 分子链可跨接裂纹两侧,形成微纤维,阻止裂纹扩展;⑤界面优化:改善水泥浆体与骨料界面粘结,减少界面过渡区缺陷。具体的,本发明中的改性粉煤灰工程材料中掺加 0.05% 的PAM,抗折强度提高 22%,粘结强度提高 35%,抗磨性提高 28%;混凝土凝固时间缩短30%-50%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of magnetic core materials, and discloses a modified fly ash engineering material, a preparation method thereof and application. One of the modified fly ash engineering materials comprises, in parts by weight, 100 parts of a base material, 0.01-0.1 parts of polyacrylamide and 0.15-0.3 parts of a concrete quick-setting agent; the base material comprises 60-65 parts of concrete and 35-40 parts of fly ash. The application has the effects of obviously improving mechanical properties and shortening the concrete setting time, and the preparation method is simple and easy to operate, and can effectively improve the on-site production capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials, specifically to a modified fly ash engineering material, its preparation method, and its application. Background Technology

[0002] Fly ash's main components are SiO2, Al2O3, and Fe2O3 (total ≥80%), belonging to the category of potentially hydraulic pozzolanic admixtures. High-quality fly ash has a loss on ignition ≤5%. It is a grayish-white to grayish-black powder, primarily composed of spherical glass microspheres, with a large specific surface area and a bulk density of 700-1000 kg / m³. High-quality fly ash has a residue of ≤12% on a 45μm square-hole sieve. Conventional fly ash possesses pozzolanic activity, morphological effects, and micro-aggregate effects, and can react with cement hydration products to generate cementitious products, improving the workability and density of concrete. Therefore, it is often used as a cement admixture in cement production or as a concrete admixture, with the common dosage in concrete reaching 25%-40%.

[0003] Based on the calcium oxide content, fly ash is divided into Class C (calcium oxide content >10%, with hydraulic properties) and Class F (calcium oxide content <10%, with pozzolanic activity). Class F is often used as a concrete admixture to replace cement in concrete, while Class C can be directly used to prepare cement.

[0004] Fly ash enhances the density, workability, and durability of concrete through its morphological, filling, and reactivity effects; however, it suffers from low early-stage strength. Specifically, fly ash concrete exhibits significantly lower strength at 3 and 7 days compared to benchmark concrete, with the effect becoming more pronounced at higher fly ash dosages, thus impacting construction progress. Furthermore, fly ash concrete exhibits reduced resistance to freezing and carbonation, greater quality fluctuations, and a higher risk of shrinkage and cracking in finished products, limiting its applicability in various scenarios. Summary of the Invention

[0005] This invention provides a modified fly ash engineering material and its preparation method to solve the problems of low early strength and reduced performance of existing fly ash concrete.

[0006] In a first aspect, the present invention provides a modified fly ash engineering material, comprising, by weight: 100 parts of base material, 0.01-0.1 parts of polyacrylamide, and 0.15-0.3 parts of concrete accelerator; the base material includes 60-65 parts of concrete and 35-40 parts of fly ash.

[0007] Concrete is composed of cement, water, fine aggregate (sand), and coarse aggregate (gravel). When necessary, admixtures (such as water-reducing agents and air-entraining agents) and additives (such as slag powder) may also be added. The main components of cement are clinker such as tricalcium silicate (C3S), dicalcium silicate (C2S), and tricalcium aluminate (C3A), supplemented with setting regulators such as gypsum.

[0008] Among them, the molecular weight of polyacrylamide directly determines its thickening ability and molecular chain bridging effect, which is a key indicator for balancing performance and workability. The appropriate molecular weight of polyacrylamide varies for different construction scenarios, as shown in Table 1 below.

[0009] Table 1

[0010] For example, the applicable scenarios for the different concrete types mentioned above can be defined by specific physicochemical properties such as specific surface area, neat cement paste fluidity (ISO 679 or GB / T 8077), mortar spread (JC / T 986 "Self-leveling Mortar"), concrete slump spread (GB / T 50080), controllable initial setting time (GB / T 1346), compressive strength at different times (refer to Appendix B of TB / T 3193 "Technical Conditions for Prestressed Tendons of Railway Engineering" and JG / T 289 "Polymer Mortar for Strengthening Concrete Structures"), air content, 28-day drying shrinkage, and absolute value of particle zeta potential in the system.

[0011] Specifically, in ①, the initial setting time is 40-120 min, the interval between initial and final setting is ≤60 min, and the initial setting fluctuation is ≤±10 min. The concrete slump is 600-750 mm, and T50 is 2-6 s; the initial fluidity of the mortar is ≥240 mm, with zero bleeding. The compressive strength is ≥15-25 MPa at 4 h, ≥40 MPa at 1 day, and ≥50 MPa at 28 days; the air content is 2-4%, and the drying shrinkage at 28 days is ≤0.06%. The mortar should refer to JC / T 985-2017, and the concrete should refer to JGJ / T 283 Self-compacting Concrete Specification. The setting time and early strength index are determined by testing.

[0012] ② In this standard, for conventional pumping, impermeable and crack-resistant concrete and ordinary mortar used in road paving, the slump is 450-600mm, and the pumping time is T50 5-12s; impermeability ≥P8. The road surface has a 28-day compressive strength of 30-45MPa and a flexural strength ≥4.0MPa; mortar fluidity is 180-220mm. The initial setting time is 180-300min, with a bleeding rate ≤2% and a drying shrinkage ≤0.08%. This standard balances workability, crack resistance, durability, and economy, making it a preferred range for general engineering applications. Pumping, impermeable and crack-resistant, road paving, and ordinary mortar standards are: Pumping JGJ / T10; Road surface JTG / TF30; Waterproof concrete GB50108; Mix proportion JGJ / T55; Mortar JGJ / T 98 and JGJ / T70 standards.

[0013] ③ In this case, it needs to be resistant to separation and bleeding, with a bleeding rate ≤1%; underwater slump 550-650mm; rapid setting of shotcrete, initial setting 2-5min; strict temperature control for large-volume applications; 28-day compressive strength 35-50MPa; impermeability ≥P10; and also consider resistance to aggregate and mud interference, erosion, and suppression of segregation and bleeding, adapting to complex and demanding construction conditions. High-drop underwater, high-mud-content aggregate, shotcrete, high-bleeding-resistant large-volume concrete: large-volume GB50496; shotcrete JGJ / T372; underwater concrete reference SL / T 352, aggregate mud content controlled according to JGJ52.

[0014] ④ For grout used in non-main structures, the setting is rapid and controllable, with initial setting in minutes to tens of minutes. The fluidity meets the requirements for grouting and filling, and the bleeding rate is close to 0. The 28-day compressive strength is 20-40 MPa. It focuses on consolidation, water stopping, and seepage prevention, without pursuing high mechanical strength. It is suitable for crack filling and curtain sealing, allowing moderate plastic deformation to meet the requirements of seepage prevention and leak plugging conditions. Leak plugging grouting and water-stopping curtain (non-main structure): Underground grouting waterproofing GB50108; grouting materials refer to JC / T 984. The curtain and leak plugging grout are mainly based on mix proportion tests; there is no dedicated national standard for concrete.

[0015] The concrete accelerator of this invention accelerates the cement hydration process and rapidly generates a setting skeleton through chemical action, while also aiding physical action, enabling concrete to set and harden in a short time. It is suitable for applications such as shotcrete and emergency repairs. The core mechanisms of its chemical and physical actions are as follows: ① Core Chemical Role: The sodium aluminate in alkaline accelerators rapidly ionizes upon contact with water, reacting with the cement hydration system. Firstly, it eliminates the retarding effect of gypsum, promoting the rapid hydration of tricalcium aluminate (C3A) in the cement. Secondly, it rapidly generates a large number of water-insoluble needle-like or network crystals (such as ettringite AFt, hydrated calcium aluminate CAH, etc.). These crystals cross-link between cement particles, forming a preliminary rigid skeleton, causing the concrete to quickly lose its fluidity and achieve initial setting. Different types of accelerators exhibit different reactions. Sodium aluminate (alkaline) accelerates the consumption of calcium sulfate, generating monosulfide hydrated calcium sulfoaluminate (AFm) and CAH, achieving flash setting. (2) Physical auxiliary effect: The quick-setting agent powder particles are small and have good dispersibility, which can be evenly distributed in the cement paste, increasing the contact area of ​​hydration reaction, reducing cement particle agglomeration, and allowing the hydration reaction to occur simultaneously and quickly; at the same time, some components can reduce the surface tension of the paste, accelerate water penetration, further improve the hydration rate, and help shorten the setting time.

[0016] Meanwhile, concrete accelerators also promote the formation of calcium silicate hydrate (CSH) gel, fill the gaps in the crystalline skeleton, form a dense structure, avoid "setting but not hardening", and ensure that the concrete quickly generates early strength after setting. At the same time, some alkali-free accelerators can optimize the pore structure, reduce harmful pores, and alleviate the loss of strength in the later stage.

[0017] The hydration-accelerating effect of concrete accelerators is highly dependent on their compatibility with concrete raw materials. Poor compatibility will directly lead to accelerator failure and insufficient strength. Therefore, the compatibility between the concrete accelerator and the cement used (mineral composition, gypsum content, fineness, and alkali content of the cement) directly determines the accelerating effect of the accelerator. A cement paste compatibility test must be completed before selecting a accelerator. For cement with high C3A content, aluminate-based and aluminum sulfate-based quick-setting agents should be preferred, as they can quickly match C3A hydration and provide a more stable quick-setting effect. For retarded cement with high gypsum content, quick-setting agents that can quickly consume soluble gypsum and counteract the retarding effect should be preferred, to avoid the retarding effect of gypsum offsetting the quick-setting effect. For low-heat cement and slag cement, alkali-free quick-setting agents with early strength activation function should be preferred to compensate for the low hydration activity of the cement itself.

[0018] In one alternative embodiment, the concrete quick-setting agent is selected as sodium aluminate.

[0019] In one optional embodiment, the fly ash has a loss on ignition ≤5%, a water requirement ratio ≤105%, and a sieve residue ≤12%.

[0020] Loss on ignition refers to the percentage reduction in mass of fly ash after burning to constant weight at 950±25℃, as specified in GB / T 1596—2017 Fly Ash for Cement and Concrete; Water requirement ratio refers to the ratio (%) of the water required for fly ash mortar (fly ash + cement + water) to the water required for reference cement mortar (pure cement + water) under the same fluidity (e.g., 130–140 mm), as specified in Appendix A of GB / T 1596; Sieve residue refers to the percentage of fly ash remaining after screening with a 45μm square-hole sieve, as specified in GB / T 1596—2017.

[0021] The compatibility selection of concrete accelerators with admixtures such as fly ash generally needs to meet the following three points: ① High fly ash content concrete (content ≥30%): Alkali-free aluminum sulfate-based quick-setting agents are preferred. Sodium aluminate can also be used, as it does not inhibit the secondary hydration of fly ash and can simultaneously activate the activity of fly ash, avoiding the problems of "early quick setting, later hydration stagnation, and strength reduction" caused by other quick-setting agents. ② High-carbon fly ash (high loss on ignition, above 5%, for example, when the loss on ignition is 5%-8%): Prioritize the use of alkali-free concrete accelerators with good dispersibility and strong anti-adsorption capacity (e.g., alkali-free aluminum sulfate) to avoid unburned carbon particles adsorbing the effective components of the accelerator, which would lead to a significant decrease in the accelerating effect. ③ Composite admixture system (fly ash + mineral powder): Prioritize composite quick-setting agents that can simultaneously activate the activity of multiple admixtures, including sodium aluminate, to ensure the hydration acceleration effect of the entire cementitious system.

[0022] At the same time, it is also necessary to confirm the compatibility of the quick-setting agent with other admixtures. For example, the quick-setting agent should not have antagonistic effects with water-reducing agents (especially polycarboxylate water-reducing agents), air-entraining agents, antifreeze agents, etc. used in concrete, and should not cause problems such as stratification, sedimentation, bleeding, failure of quick-setting effect, or deterioration of workability.

[0023] It is also necessary to confirm the compatibility of the accelerator with the mixing water and aggregates, that is, whether there is any antagonistic effect between it and the components in the mixing water and aggregates. For example, for concrete mixed with seawater or groundwater, it is necessary to confirm that chloride ions, sulfate ions, etc. in the water will not cause side reactions with the effective components of the accelerator to avoid accelerating the decline of its effect; for reactive aggregate concrete, high-alkali accelerators are strictly prohibited, and alkali-free and potassium-free accelerators should be preferred to avoid accelerating the alkali-aggregate reaction and causing concrete expansion and cracking.

[0024] Secondly, the present invention also provides a method for preparing modified fly ash engineering materials, comprising: mixing fly ash and concrete (e.g., adding concrete with fly ash as a base), maintaining stirring, and then adding polyacrylamide and concrete accelerator in sequence, and continuing to stir after all additions to obtain modified fly ash engineering materials.

[0025] Thirdly, the present invention also provides the application of modified fly ash engineering materials in construction engineering at sites that generate fly ash.

[0026] Its preferred application is in the construction engineering of thermal power plant ash disposal sites.

[0027] For example, it can be used in the renovation and heightening of thermal power plant ash yards.

[0028] This invention utilizes fly ash in the site as one of the main materials to improve the properties of fly ash concrete at a lower cost, enhancing its load-bearing capacity, compressive and shear strength, and making it more suitable for construction. At the same time, it increases the hardening and forming rate, effectively improving construction efficiency and accelerating the construction progress.

[0029] The technical solution of this invention has the following advantages: 1. This invention provides a modified fly ash engineering material, comprising, by weight: 100 parts of base material, 0.01-0.1 parts of polyacrylamide, and 0.15-0.3 parts of concrete accelerator; the base material includes 60-65 parts of concrete and 35-40 parts of fly ash. The concrete provides the main strength, adhesion, and formability; the active SiO2 and Al2O3 in the fly ash react with the calcium hydroxide Ca(OH)2 produced during cement hydration under alkaline activation to undergo a secondary hydration reaction, generating cementitious products such as hydrated calcium silicate (CSH) and hydrated calcium aluminate; these products continuously fill pores and enhance interfacial bonding, enabling the concrete to continuously increase its later-stage strength and compensating for the low early-stage strength. The polyacrylamide (PAM) added in this invention achieves the following functions through its unique molecular structure and interaction with the cement system: ① Adsorption and dispersion: Long-chain molecules adsorb onto the surface of cement particles, reducing electrostatic repulsion between particles through charge neutralization, thus promoting flocculation and aggregation; ② Network formation: Interwoven molecular chains form a three-dimensional network structure, encapsulating water molecules and enhancing the cohesiveness of the cement paste; ③ Hydration regulation: [The text abruptly ends here, likely due to an incomplete sentence or missing information.] + The hydration products form complexes, affecting the cement hydration process and product morphology; ④ Crack bridging: When concrete cracks under external force, PAM molecular chains can bridge the cracks on both sides, forming microfibers and preventing crack propagation; ⑤ Interface optimization: Improves the bonding between cement paste and aggregate interface, reducing defects in the interface transition zone. Specifically, the modified fly ash engineering material of this invention, with the addition of 0.05% PAM, increases flexural strength by 22%, bond strength by 35%, and abrasion resistance by 28%; the concrete setting time is shortened by 30%-50%.

[0030] 2. The preparation method provided by this invention is simple and easy to operate, can improve on-site production capacity, and effectively provides a high-performance, easy-to-process modified fly ash engineering material. Detailed Implementation

[0031] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.

[0032] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0033] Example 1 A modified fly ash engineering material comprises: 0.05 parts polyacrylamide, 0.2 parts concrete accelerator, 62 parts concrete, and 38 parts fly ash, with 1 part by weight equaling 1 kg.

[0034] Its preparation method includes: 1. Obtain concrete, fly ash, polyacrylamide, and concrete accelerator separately; The concrete consists of 240 kg of cement, 120 kg of water, 430 kg of fine aggregate (sand passing through a 350 μm sieve), and 698 kg of coarse aggregate (stones with a diameter of 5–20 mm).

[0035] The fly ash is fly ash with a loss on ignition ≤5%, water demand ratio ≤105%, and sieve residue ≤12%. In this embodiment, the fly ash is fly ash from the site of a thermal power plant ash yard, with a loss on ignition of 4.5%, water demand ratio of 103%, and sieve residue of 11.0%. The molecular weight (Mw) of polyacrylamide is 1.0 × 10⁻⁶. 7 g / mol; Sodium aluminate is used as the concrete quick-setting agent.

[0036] 2. According to the weight ratio of 0.05 parts polyacrylamide, 0.2 parts concrete accelerator, 62 parts concrete, and 38 parts fly ash, first add the fly ash as a base to the concrete and keep stirring. Then add the polyacrylamide and concrete accelerator in sequence. After all the materials are added, continue stirring for 10 minutes to obtain the modified fly ash engineering material.

[0037] Example 2 A modified fly ash engineering material differs from Example 1 in that it contains 0.01 parts polyacrylamide and 0.15 parts concrete quick-setting agent.

[0038] Its preparation method includes: 1. Obtain concrete, fly ash, polyacrylamide, and concrete accelerator separately; The concrete consists of 240 kg of cement, 120 kg of water, 430 kg of fine aggregate (sand passing through a 350 μm sieve), and 698 kg of coarse aggregate (stones with a diameter of 5–20 mm).

[0039] The fly ash is fly ash with a loss on ignition ≤5%, water demand ratio ≤105%, and sieve residue ≤12%. In this embodiment, the fly ash is fly ash from the site of a thermal power plant ash yard, with a loss on ignition of 4.5%, water demand ratio of 103%, and sieve residue of 11.0%. The molecular weight (Mw) of polyacrylamide is 1.0 × 10⁻⁶. 7 g / mol; Sodium aluminate is used as the concrete quick-setting agent.

[0040] 2. According to the weight ratio of 0.01 parts polyacrylamide, 0.15 parts concrete accelerator, 62 parts concrete, and 38 parts fly ash, first add the fly ash as a base to the concrete and keep stirring. Then add the polyacrylamide and concrete accelerator in sequence. After all the materials are added, continue stirring for 10 minutes to obtain the modified fly ash engineering material.

[0041] Example 3 A modified fly ash engineering material differs from Example 1 in that it contains 0.1 parts polyacrylamide and 0.3 parts concrete quick-setting agent.

[0042] Its preparation method includes: 1. Obtain concrete, fly ash, polyacrylamide, and concrete accelerator separately; The concrete consists of 240 kg of cement, 120 kg of water, 430 kg of fine aggregate (sand passing through a 350 μm sieve), and 698 kg of coarse aggregate (stones with a diameter of 5–20 mm).

[0043] The fly ash is fly ash with a loss on ignition ≤5%, water demand ratio ≤105%, and sieve residue ≤12%. In this embodiment, the fly ash is fly ash from the site of a thermal power plant ash yard, with a loss on ignition of 4.5%, water demand ratio of 103%, and sieve residue of 11.0%. The molecular weight (Mw) of polyacrylamide is 1.0 × 10⁻⁶. 7 g / mol; Sodium aluminate is used as the concrete quick-setting agent.

[0044] 2. According to the weight ratio of 0.1 parts polyacrylamide, 0.3 parts concrete accelerator, 62 parts concrete, and 38 parts fly ash, first add the fly ash as the base to the concrete and keep stirring. Then add the polyacrylamide and concrete accelerator in sequence. After all the materials are added, continue stirring for 10 minutes to obtain the modified fly ash engineering material.

[0045] Example 4 A modified fly ash engineering material differs from Example 1 in that it contains 65 parts concrete and 35 parts fly ash.

[0046] Its preparation method includes: 1. Obtain concrete, fly ash, polyacrylamide, and concrete accelerator separately; The concrete consists of 240 kg of cement, 120 kg of water, 430 kg of fine aggregate (sand passing through a 350 μm sieve), and 698 kg of coarse aggregate (stones with a diameter of 5–20 mm).

[0047] The fly ash is fly ash with a loss on ignition ≤5%, water demand ratio ≤105%, and sieve residue ≤12%. In this embodiment, the fly ash is fly ash from the site of a thermal power plant ash yard, with a loss on ignition of 4.5%, water demand ratio of 103%, and sieve residue of 11.0%. The molecular weight (Mw) of polyacrylamide is 1.0 × 10⁻⁶. 7 g / mol; Sodium aluminate is used as the concrete quick-setting agent.

[0048] 2. According to the weight ratio of 0.05 parts polyacrylamide, 0.2 parts concrete accelerator, 65 parts concrete, and 35 parts fly ash, first add the fly ash as a base to the concrete and keep stirring. Then add the polyacrylamide and concrete accelerator in sequence. After all the materials are added, continue stirring for 10 minutes to obtain the modified fly ash engineering material.

[0049] Example 5 A modified fly ash engineering material differs from Example 1 in that it contains 60 parts concrete and 40 parts fly ash.

[0050] Its preparation method includes: 1. Obtain concrete, fly ash, polyacrylamide, and concrete accelerator separately; The concrete consists of 240 kg of cement, 120 kg of water, 430 kg of fine aggregate (sand passing through a 350 μm sieve), and 698 kg of coarse aggregate (stones with a diameter of 5–20 mm).

[0051] The fly ash is fly ash with a loss on ignition ≤5%, water demand ratio ≤105%, and sieve residue ≤12%. In this embodiment, the fly ash is fly ash from the site of a thermal power plant ash yard, with a loss on ignition of 4.5%, water demand ratio of 103%, and sieve residue of 11.0%. The molecular weight (Mw) of polyacrylamide is 1.0 × 10⁻⁶. 7 g / mol; Sodium aluminate is used as the concrete quick-setting agent.

[0052] 2. According to the weight ratio of 0.05 parts polyacrylamide, 0.2 parts concrete accelerator, 60 parts concrete, and 40 parts fly ash, first add the fly ash as a base to the concrete and keep stirring. Then add the polyacrylamide and concrete accelerator in sequence. After all the materials are added, continue stirring for 10 minutes to obtain the modified fly ash engineering material.

[0053] Example 6 A modified fly ash engineering material differs from Example 1 in that: the concrete uses a C35 strength grade mix proportion, the amount of concrete accelerator is adjusted to 0.25 parts, and the molecular weight of polyacrylamide is 1.2 × 10⁻⁶. 7 g / mol (anionic type, i.e., 12 million).

[0054] Its preparation method includes: 1. Obtain concrete, fly ash, polyacrylamide, and concrete accelerator separately; The concrete consists of 280 kg of cement, 125 kg of water, 410 kg of fine aggregate (sand passing through a 300 μm sieve), and 705 kg of coarse aggregate (stones with a diameter of 5–25 mm).

[0055] The fly ash is fly ash with a loss on ignition ≤5%, water demand ratio ≤105%, and sieve residue ≤12%. In this embodiment, the fly ash is fly ash from the site of a thermal power plant ash yard, with a loss on ignition of 4.5%, water demand ratio of 103%, and sieve residue of 11.0%. The molecular weight (Mw) of polyacrylamide is 1.2 × 10⁻⁶. 7 g / mol; Sodium aluminate is used as the concrete quick-setting agent.

[0056] 2. According to the weight ratio of 0.05 parts polyacrylamide, 0.25 parts concrete accelerator, 62 parts concrete, and 38 parts fly ash, first add the fly ash as the base to the concrete and keep stirring. Then add the polyacrylamide and concrete accelerator in sequence. After all the materials are added, continue stirring for 10 minutes to obtain the modified fly ash engineering material.

[0057] Example 7 A method for preparing a modified fly ash engineering material differs from Example 1 in that: The difference from Example 1 is that mineral powder is added to the concrete, and the concrete accelerator is a sodium aluminate-aluminum sulfate composite accelerator (0.22 parts). The molecular weight of the polyacrylamide is 8.0 × 10⁻⁶. 6 g / mol (anionic type, i.e., 8 million).

[0058] Its preparation method includes: 1. Obtain concrete, fly ash, polyacrylamide, and concrete accelerator separately; The concrete consists of 200 kg of cement, 115 kg of water, 440 kg of fine aggregate (sand with a particle size passing through a 350 μm sieve), 685 kg of coarse aggregate (stones with a diameter of 5–20 mm), and 80 kg of mineral powder (S95 grade granulated blast furnace slag powder with a particle size of 12 μm).

[0059] The fly ash is fly ash with a loss on ignition ≤5%, water demand ratio ≤105%, and sieve residue ≤12%. In this embodiment, the fly ash is fly ash from the site of a thermal power plant ash yard, with a loss on ignition of 4.5%, water demand ratio of 103%, and sieve residue of 11.0%. The molecular weight (Mw) of polyacrylamide is 8 × 10⁻⁶. 6 g / mol; The concrete accelerator is a sodium aluminate-aluminum sulfate composite accelerator.

[0060] 2. According to the weight ratio of 0.05 parts polyacrylamide, 0.22 parts concrete accelerator, 62 parts concrete, and 38 parts fly ash, first add the fly ash as a base to the concrete and keep stirring. Then add the polyacrylamide and concrete accelerator in sequence. After all the materials are added, continue stirring for 10 minutes to obtain the modified fly ash engineering material.

[0061] Example 8 A method for preparing modified fly ash engineering materials differs from Example 1 in that: high-carbon fly ash with a loss on ignition higher than 5% (loss on ignition is 8.5%, water requirement ratio is 108%, and residue on a 45μm square-hole sieve is 15%) is used; alkali-free aluminum sulfate accelerator is selected as the concrete accelerator (dosage is 0.25 parts); and the polyacrylamide has a molecular weight of 1.2 × 10⁻⁶. 7 g / mol (anionic type, i.e., 12 million).

[0062] Its preparation method includes: 1. Obtain concrete, fly ash, polyacrylamide, and concrete accelerator separately; The concrete consists of 240 kg of cement, 120 kg of water, 430 kg of fine aggregate (sand passing through a 350 μm sieve), and 698 kg of coarse aggregate (stones with a diameter of 5–20 mm).

[0063] The fly ash in this embodiment is fly ash from a thermal power plant ash yard, with a loss on ignition of 8.5%, a water requirement ratio of 108%, and a sieve residue of 15%. The molecular weight (Mw) of polyacrylamide is 1.2 × 10⁻⁶. 7 g / mol; The concrete quick-setting agent is alkali-free aluminum sulfate.

[0064] 2. According to the weight ratio of 0.05 parts polyacrylamide, 0.25 parts concrete accelerator, 62 parts concrete, and 38 parts fly ash, first add the fly ash as the base to the concrete and keep stirring. Then add the polyacrylamide and concrete accelerator in sequence. After all the materials are added, continue stirring for 10 minutes to obtain the modified fly ash engineering material.

[0065] Comparative Example 1 A method for preparing a modified fly ash engineering material differs from Example 1 in that it only contains concrete and fly ash, with the same weight percentages of each component.

[0066] Comparative Example 2 A method for preparing a modified fly ash engineering material differs from Example 1 in that it only contains concrete, fly ash, and sodium aluminate, with each component having the same weight percentage.

[0067] Comparative Example 3 A method for preparing a modified fly ash engineering material differs from Example 6 in that it only contains concrete, fly ash, and sodium aluminate, with each component having the same weight percentage.

[0068] Comparative Example 4 A method for preparing a modified fly ash engineering material differs from Example 7 in that it only contains concrete, fly ash, and sodium aluminate, with each component having the same weight percentage.

[0069] Comparative Example 5 A method for preparing a modified fly ash engineering material differs from Example 8 in that it only contains concrete, fly ash, and sodium aluminate, with each component having the same weight percentage.

[0070] Experimental Example The modified fly ash engineering materials prepared in the examples and comparative examples were tested for bond strength, concrete setting time, flexural strength, and abrasion resistance according to the specifications in GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures", and DL / T 5150-2017 "Test Procedures for Hydraulic Concrete". The specific test methods are as follows: Bond strength: Splitting tensile strength test method.

[0071] Concrete setting time: Penetration resistance method.

[0072] Flexural strength: Three-point loading method.

[0073] Abrasion resistance: Impact abrasion test (ring method).

[0074] The detection results of the embodiments and comparative examples of the present invention are shown in Tables 2 and 3 below.

[0075] Table 2

[0076] Table 3

[0077] The data in Tables 2 and 3 show that the bonding strength, flexural strength, abrasion resistance, and setting time of each embodiment are significantly better than those of the corresponding comparative examples, indicating that the combined use of polyacrylamide (PAM) and concrete accelerator can significantly improve the comprehensive performance of modified fly ash engineering materials.

[0078] The results of the comparison between Example 1 (basic formulation) and Comparative Example 1 (blank sample) are shown in Table 5 below: Table 5

[0079] A comparison between Example 1 and Comparative Example 2 (accelerator only, no PAM added) shows that: The core function of the accelerator is to reduce the setting time from 480 min to 300 min (a reduction of 37.5%), primarily responsible for rapid setting. PAM's core function is to increase bond strength from 2.1 MPa to 2.7 MPa (+28.6%), flexural strength from 4.7 MPa to 5.5 MPa (+17.0%), and abrasion rate from 3.3 to 2.5 kg / m² (-24.2%), primarily responsible for improving mechanical properties and durability.

[0080] The combination of the two further shortens the setting time to 288 min, achieving a synergistic effect of "rapid setting + high strength".

[0081] The comparison of Examples 1-3 shows that the effects of the dosage of admixture polyacrylamide and concrete accelerator on the performance of concrete are as follows: within the range of 0.01-0.1 parts (PAM) and 0.15-0.3 parts (accelerator), the various properties improve with the increase of dosage, and the setting time shortens with the increase of dosage, showing a clear dose-dependent relationship.

[0082] The effects of fly ash content on concrete performance in Examples 1 and 4-5 show that as fly ash content increases, setting time increases, while mechanical properties and durability decrease.

[0083] The performance comparison of different systems in Examples 1 and 6-8 shows that C35 high-strength concrete in Example 6 has the shortest setting time, the best mechanical and durability properties, and the best overall performance. In the mineral powder composite concrete in Example 7, the mineral powder activity activation effect is good. In the high carbon ash + alkali-free quick-setting agent in Example 8, the setting time is less than 300 min, the bond strength reaches 2.4 MPa, the flexural strength reaches 5 MPa, the abrasion resistance (wear amount) reaches 2.8 kg / m², and the high carbon ash has good compatibility.

[0084] A comparison between Example 8 and Comparative Example 5 shows that, for the high-carbon fly ash (loss on ignition 8.5%) system, the selection of concrete accelerators yields the following results, as shown in Table 6: Table 6

[0085] The results in Table 6 show that unburned carbon particles in high-carbon fly ash can adsorb the effective components of alkaline accelerators, leading to accelerator failure. Using alkali-free aluminum sulfate accelerators can effectively avoid carbon adsorption problems, restore accelerator and enhancement effects, and verify the correctness of the accelerator selection principle in this paper.

[0086] This invention achieves significant improvements in mechanical properties by 20%–35% and a reduction in setting time by 30%–40% under conditions of high fly ash content of 35–40 parts by combining PAM with an accelerator. Furthermore, by selecting appropriate accelerators, it can cover various raw material scenarios such as high-quality fly ash, mineral powder-containing composite fly ash, and high-carbon fly ash, thus possessing good engineering applicability.

[0087] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A modified fly ash engineering material, characterized in that, By weight, it includes: 100 parts of base material, 0.01-0.1 parts of polyacrylamide, and 0.15-0.3 parts of concrete accelerator; the base material includes 60-65 parts of concrete and 35-40 parts of fly ash.

2. The modified fly ash engineering material according to claim 1, characterized in that, The concrete quick-setting agent is sodium aluminate.

3. The modified fly ash engineering material according to claim 1, characterized in that, The fly ash has a loss on ignition of ≤5%, a water requirement ratio of ≤105%, and a sieve residue of ≤12%.

4. The modified fly ash engineering material according to claim 1, characterized in that, When the loss on ignition of the fly ash is 5%-8%, the concrete accelerator is an alkali-free concrete accelerator.

5. The modified fly ash engineering material according to claim 4, characterized in that, The concrete quick-setting agent is alkali-free aluminum sulfate.

6. The modified fly ash engineering material according to claim 1, characterized in that, When the concrete contains mineral powder, a composite quick-setting agent is used, and the composite quick-setting agent includes sodium aluminate.

7. The method for preparing the modified fly ash engineering material according to any one of claims 1-6, characterized in that, include: Fly ash is mixed with concrete while stirring. Then, polyacrylamide and concrete accelerator are added in sequence. After all the ingredients are added, stirring is continued to obtain modified fly ash engineering materials.

8. The application of the modified fly ash engineering material according to any one of claims 1-6 or the modified fly ash engineering material prepared by the preparation method according to claim 7 in the construction engineering of sites that generate fly ash.

9. The application according to claim 8, characterized in that, The site where fly ash is generated is a thermal power plant ash field.

10. The application according to claim 8, characterized in that, The construction projects include building renovation and height increase projects.